2001
DOI: 10.1093/oxfordjournals.molbev.a003860
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny and Divergence Time Estimates for Major Rodent Groups: Evidence from Multiple Genes

Abstract: The order Rodentia contains half of all extant mammal species, and from an evolutionary standpoint, there are persistent controversies surrounding the monophyly of the order, divergence dates for major lineages, and relationships among families. Exons of growth hormone receptor (GHR) and breast cancer susceptibility (BRCA1) genes were sequenced for a wide diversity of rodents and other mammals and combined with sequences of the mitochondrial 12S rRNA gene and previously published sequences of von Willebrand fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(193 citation statements)
references
References 72 publications
12
175
2
4
Order By: Relevance
“…It was also suggested that the faster evolution reported for mouse gene sequences (based on analysis of substitutions of amino acids and each of three codon positions for three protein-coding genes, and of a ribosomal RNA; ref. 33) compared with other mammals concurs with the deterministicstochastic hypothesis (32). However, rapid sequence evolution in the mouse lineage is well known, and need not indicate a release of selection, but, rather, is likely an effect of their short generation time (34,35).…”
Section: Evaluation Of the Pgc-specification Hypothesissupporting
confidence: 72%
“…It was also suggested that the faster evolution reported for mouse gene sequences (based on analysis of substitutions of amino acids and each of three codon positions for three protein-coding genes, and of a ribosomal RNA; ref. 33) compared with other mammals concurs with the deterministicstochastic hypothesis (32). However, rapid sequence evolution in the mouse lineage is well known, and need not indicate a release of selection, but, rather, is likely an effect of their short generation time (34,35).…”
Section: Evaluation Of the Pgc-specification Hypothesissupporting
confidence: 72%
“…The range recognizes that L1 extinction could have occurred as recently as the divergence time of megabat species from each other or as far back as the divergence of the megabat lineage from the rest of the Yinpterochiroptera (Figure 1). This rate can be compared to the neutral substitution rates in human, mouse, and rat (Rat Genome Sequencing Project Consortium 2004), if the divergence of human from these rodent lineages is assumed to be 87 MYA and the divergence of mouse from rat is assumed to be 9-23 MYA (Adkins et al 2001(Adkins et al , 2003Springer et al 2003;Steppan et al 2004). These divergence times give a relatively slow human rate of 0.15%/MY, and faster mouse and rat rates of 0.36-0.92%/MY, and 0.40-1.01%/MY, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The BRCA1 gene was selected for analysis because it had given robust resolution of relationships at varying levels of divergence in previous studies (Adkins et al, 2001) and was easily amplified. C. glareolus and C. rufocanus samples from Omsk (CG/AF1946, CG191, CG193, CG324, CRF179, CRF302 and CRF443) were randomly selected and 497 nt fragments of their BRCA1 genes were compared.…”
Section: Nuclear Dna Analysismentioning
confidence: 99%